2015
DOI: 10.1016/j.spinee.2015.06.060
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer screening for deep venous thrombosis in traumatic cervical spinal injuries

Abstract: D-dimer levels may be used to predict the likelihood of DVT development in patients with acute cervical SCI. Furthermore, the optimal timing for screening test by D-dimer is 2 weeks after injury, and optimal threshold level for D-dimer for diagnosing DVT is 16 μg/dL. Such a screening test would be cost-efficient and simple to administer and could then be followed with additional investigations, such as ultrasonography or venography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
1
22
1
1
Order By: Relevance
“…Masuda et al . found that all DVT‐positive patients with traumatic cervical spinal injuries had severe paralysis classified as C or greater on the ASIA Impairment Scale, and another study suggested that DVT can develop in the very acute stage of SCI and that the incidence increases with more severe paralysis . In contrast to those findings, we did not find any correlation between DVT and ASIA score.…”
Section: Discussioncontrasting
confidence: 99%
“…Masuda et al . found that all DVT‐positive patients with traumatic cervical spinal injuries had severe paralysis classified as C or greater on the ASIA Impairment Scale, and another study suggested that DVT can develop in the very acute stage of SCI and that the incidence increases with more severe paralysis . In contrast to those findings, we did not find any correlation between DVT and ASIA score.…”
Section: Discussioncontrasting
confidence: 99%
“…Niikura et al 17. showed that the incidence of VTE in Japanese patients with pelvic and/or lower extremity fractures was 19%, whereas Masuda et al 18. showed that the incidence of DVT with cervical spinal cord injury was 10%.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Three observational studies examined the role of D-dimer as a screening marker for VTE in patients with SCI. [20][21][22] Two studies reported no difference in D-dimer values in SCI patients who developed VTE compared with those without any events in acute 20 or chronic 21 phases after injury. Another study reported that D-dimer can be utilized as a surrogate marker to predict the likelihood of developing DVT in patients with cervical SCI, and concluded that the optimal timing of performing a D-dimer test should be 2 weeks after injury.…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%
“…Another study reported that D-dimer can be utilized as a surrogate marker to predict the likelihood of developing DVT in patients with cervical SCI, and concluded that the optimal timing of performing a D-dimer test should be 2 weeks after injury. 22 However, the D-dimer levels were only reported for patients with VTE, were not compared with those without VTE, and the findings were confined to the cervical level only, which has been reported to have the lowest risk of VTE among spinal cord levels. 16 Given that blood coagulation is very frequently activated and activation of fibrinolysis is also commonplace after acute trauma, most patients with SCI may have elevated D-dimer values, which can result in an increase in imaging tests performed and unnecessary treatment of potentially clinically insignificant findings.…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%